Penegakan Hukum Terhadap Perlindungan Hutan Oleh Polisi Kehutanan - Andi Ahmad Afandy Lutfi; Abdillah AR (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to determine the efforts made by the Forestry Police at the Lejja Natural Tourism Park resort to protect forests from illegal logging in Soppeng Regency and to find out the responsibilities of the Forestry Police in enforcing laws against forest protection from illegal logging. The research method used is normative and empirical, so the relevant approaches are the statutory and social approaches. The Legislative Approach is an approach that is taken by examining all laws and regulations that are related to the legal issues being handled while the Social Approach is an approach that is taken in order to establish communication and foster participation from the community. Based on research data and discussion From the results obtained, it can be concluded that: first, in carrying out their duties, the efforts made by the forestry police at the Lejja Nature Tourism Park Resort, Soppeng Regency are preventive, namely routine forestry police patrol activities to prevent illegal logging and always involve the surrounding community to work together or work together in protecting and preserving forests, repressive in nature seeks to enforce the rule of law against suspects or perpetrators of illegal logging but there are stages that the forestry police must need to make it easier to catch perpetrators by securing evidence through documentation of areas where illegal logging has occurred. Second, the responsibility of the Forestry Police of the Lejja Nature Tourism Park Resort, Soppeng Regency is based on the Regulation of the Minister of Forestry of the Republic of Indonesia Number P.75/Menhut-II/2014 concerning the Forestry Police in Article 4 and being the front guard in eradicating all types of unlawful acts related to forests, forest areas and forest products.